2020
DOI: 10.21674/2448-0479.63.193-197
|View full text |Cite
|
Sign up to set email alerts
|

Estaquia caulinar de Rubus erythrocladus Mart. ex Hook.f em diferentes concentrações de ácido indolbutírico

Abstract: O arbusto Rubus erythrocladus Mart. ex Hook.f. (amora-verde) é uma espécie endêmica do Brasil e uma das plantas alimentícias não convencionais que apresenta grande potencial de uso, devido ao sabor agradável de seus frutos e às altas concentrações de flavonoides. O objetivo deste estudo foi avaliar o efeito de diferentes concentrações de AIB no enraizamento de estacas caulinares de R. erythrocladus. O experimento foi realizado em casa de vegetação no IFRS – Campus Sertão, durante o período de novembro de 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…The results found in this study regarding rooting of cuttings are also lower than that of Balestrin et al [9], in which a rooting of 60.0% in cuttings of R. erythroclados of 10 cm treated with 1.000 mg L -1 of IBA. Such discrepancy may be due to the time of year when cuttings were collected from the mother plants.…”
Section: Table 1 Percentages Of Live Cuttings Atcontrasting
confidence: 90%
See 3 more Smart Citations
“…The results found in this study regarding rooting of cuttings are also lower than that of Balestrin et al [9], in which a rooting of 60.0% in cuttings of R. erythroclados of 10 cm treated with 1.000 mg L -1 of IBA. Such discrepancy may be due to the time of year when cuttings were collected from the mother plants.…”
Section: Table 1 Percentages Of Live Cuttings Atcontrasting
confidence: 90%
“…Although the study by Balestrin et al [9] showed a greater rooting when cuttings are collected in late spring, it is important to note that the R. erythroclados plants are in the reproductive phase during this season. Therefore, the propagation by stem cuttings can significantly compromise fruit production, since it removes the branches from the plant that are potential fruit producers.…”
Section: Table 1 Percentages Of Live Cuttings Atmentioning
confidence: 90%
See 2 more Smart Citations